The Relationship Between Diabetes and Depression - Chowdhury, Sumon Rahman; Barua, Shangkar; Kamal, Abu Hena Mostafa (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Evidence of a bidirectional relationship between depression and diabetes has recently been documented in large prospective studies. Comorbid depression is associated with an increased risk of poor glycemic control, diabetes complications and mortality. Moreover, incident diabetes has also been found to be risk factors for subsequent development of depressive episodes. Furthermore, in a recent systematic review, depression is associated with the subsequent development of T2DM by up to 37% as it causes central obesity, increased release of circulating corticosteroid hormone (which antagonizes the action of insulin) and insulin resistance that is a more common etiological pathway for the development of T2DM. Subsequently, the presence of depression with diabetes has a severe impact for self-care management and long term outcome which includes long term disturbance of mood. Therefore, the purpose of this review is to explain the bidirectional relationship between diabetes and depression and explore the management options that are advocated to enhance the Diabetes self-management education and improve the quality of life for diabetic patients with depression Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 50-54